Pengaruh Fee Audit, Rotasi Kap, dan Reputasi Auditor Terhadap Kualitas Audit (Studi Empiris pada Perusahan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2007-2012) - Pamungkas, Yohanes Chrisostomus Catur (JRMA | Jurnal Riset Manajemen dan Akuntansi, 2014)
This study aimed to examine audit fee, accounting firm rotation, and auditor reputation effect on the audit quality in manufacturing company listed on the Indonesia Stock Exchange in 2007 until 2012. This study used audited financial statement of manufacturing company listed on the Indonesia Stock Exchange in 2007 until 2012. Samples are 25 of 153 manufacturing company listed on the Indonesia Stock Exchange in 2007 until 2012. Sample selection purposive sampling method. The result of multiple linear regression’s SPSS 17 showed that audit fee variable have a significant effect on audit quality, while accounting firm rotation and auditor reputation had no significant effect on audit quality. This result showed that the higher fees audit will increase audit quality. Otherwise, accounting firm rotation and auditor reputation of The Big Four not always have an effect on the audit quality.